PENYAKIT PEKERJA DALAM KEGIATAN EKSPLOITASI HUTAN DI KALIMANTAN TENGAH - Soenarno Soenarno; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Working conditions in tropical forests especially in logging. are generally difficult. The materials handled are heavy, outdoor weather conditions are unpredicted. the growth of vegetation are commonly dense, and temperature and humidity are mostly high. These conditions. together with inappropriate workers' facilities and nutrient will lead to bad health conditions and occurence of various illnesses.An investigation carried out in two logging companies in Central Kalimantan revealed that there are 8 kinds of illnesses that are commonly suffered by workers, i.e : influenza, malaria, irritation of respiratory systems, feeling of nausea, back and neck problems, headache/giddiness, sore eyes, and skin disease. The highest risk of having illness is for those working in transportation operations, followed by felling, skidding and workshop. It is also found that the least risk is timber cruising activity.